Model of electromagnetic interactions in LTE network - Коляденко, Ю.Ю.; Чурсанов, Н.А.; Бондаренко, О.С. (Radiotekhnika, 2019)
A mathematical model of electromagnetic interactions in the groups of radio electronic networks of the LTE network has been developed. This model consists of a model of placement and movement of radio electronic means (subscriber terminals) of the network. The use of a shaping filter for changing the ATs coordinates has been proposed as a model for the AT locating and moving. The model of electromagnetic interactions also consists of a model of signals propagation in communication lines, which takes into account the transmitter power, transmitting and receiving antennas gain, attenuation in free space with varying distances, efficiency of the receiving and transmitting feeders, additional attenuation caused by the influence of walls, floors overlaps, random component of additional attenuation (fast and slow fading).